PERKEMBANGAN BIAKAN SECARA VEGETATIF - Nabila Aulia Ramadhani; Siti Nurainun; Fiza Ikramullah Lubis; Nurul Hasanah (JURNAL ILMIAH NUSANTARA, 2025)
Vegetative propagation is a method of asexual reproduction in plants that allows the propagation of new individuals that are genetically identical to their parents, without the involvement of gametes or seeds.This study aims to explore the concepts, types, applications, advantages, and challenges of vegetative propagation as a method of plant reproduction that does not involve gamete fusion. Using a literature review approach, two main categories are examined: natural vegetative propagation (rhizomes, stolons, tubers, bulbs, root tubers, adventitious buds, and bulbils) and artificial methods (cuttings, layering, grafting, budding, and tissue culture). Each technique offers advantages in accelerating growth, preserving superior genetic traits, and propagating plants that are difficult to reproduce sexually. The application of vegetative propagation is essential in modern agriculture, horticulture, conservation of rare species, and the development of disease-resistant varieties. However, limitations such as genetic uniformity, risk of systemic disease transmission, and high initial costs—especially in advanced techniques like tissue culture—must be considered. Therefore, selecting an appropriate method should align with cultivation goals and resource availability to support sustainable agriculture.